Let’s check both sides of the math problem step by step.

First, we’ll do the left side: \(8 \cdot 3 + 2 \cdot 6\)

1. First, we find \(8 \cdot 3\):
- \(8 \cdot 3 = 24\)

2. Next, we find \(2 \cdot 6\):
- \(2 \cdot 6 = 12\)

Now, we add those two results together:
\[ 24 + 12 = 36 \]

So the left side equals \(36\).

Now, let’s do the right side: \(60 \div 5 \cdot 3\)

1. First, we divide \(60 \div 5\):
- \(60 \div 5 = 12\)

2. Now we multiply that result by \(3\):
- \(12 \cdot 3 = 36\)

So the right side also equals \(36\).

Now we can compare both sides:

- Left side: \(36\)
- Right side: \(36\)

Since both sides are equal, we can say:

\[ 36 \; \text{is the same as} \; 36 \]

The correct sign to put in the middle is \(=\).

So the answer is \(=\).

make tis way smaller

1 answer

Let's simplify the problem step by step.

Left Side: \(8 \cdot 3 + 2 \cdot 6\)

  1. Calculate \(8 \cdot 3 = 24\)
  2. Calculate \(2 \cdot 6 = 12\)
  3. Add the results: \(24 + 12 = 36\)

Right Side: \(60 \div 5 \cdot 3\)

  1. Calculate \(60 \div 5 = 12\)
  2. Multiply by \(3\): \(12 \cdot 3 = 36\)

Comparison:

  • Left side: \(36\)
  • Right side: \(36\)

Both sides are equal, so we write:
\[ 36 = 36 \]